RASIONAL TANPA MENJADI LIBERAL : MENJAWAB TANTANGAN LIBERALISASI PEMIKIRAN ISLAM - Hamid Fahmy Zarkasyi; Mohammad Syam'un Salim (Institute for the Study of Islamic Thought and Civilization, 2021)
On liberalism and religious pluralism from Islamic perspective and Islamic study in Indonesia; collection of articles.